DAMPAK INSTRUKSI BUPATI TENTANG ZAKAT PROFESI TERHADAP PEGAWAI DAN PENGELOLAAN ZAKAT DI BAZIS KABUPATEN BOGOR - Kurniawan, Muhammad Jimmy; Sobari, Ahmad (IBN KHALDUN BOGOR, 2013)
Zakat is worship maaliyah ijtima'iyah which has a very important position, strategic, and decisive, both in terms of Islam and of the welfare of the development side. As a subject of worship, charity, including one of the pillars (the third pillar) of the five pillars of Islam, as expressed in various hadith of the Prophet, so its presence is considered as Ma'lum minad-deen bidharuurah or their recognized automatically and an essential part of the Islamic someone.